Characteristics of Co–Ca catalyzed coal hydrogasification in a mixture of H2 and CO2 atmosphere. (15th September 2022) - Feng, Jun; Yan, Shuai; Zhang, Rong; Gu, Sumin; Qu, Xuan; Bi, Jicheng
Graphical abstract: Highlights: The feasibility of using H2 and CO2 mixture instead of pure H2 for CCHG was trailed. The concurrence of coal hydrogasification with CO2 methanation boosted CH4 production. Efficient conversions of CO2 and coal in one gasifier at 850 °C were realized. Co–Ca loaded residual coal catalyzed CO2 methanation to an equilibrium extent. The mechanism of CO2 on coal catalytic hydrogasification was preliminary revealed. CCHG : Coal catalytic hydrogasification. Abstract: Coal catalytic hydrogasification (CCHG) is a promising approach for producing substituted natural gas by using pure hydrogen as a gasifying agent. If pure hydrogen could be replaced by cheaper crude gas from the coal gasifier, the economy of CCHG would be significantly improved. However, the composition of crude gas is complicated because in addition to H2, CO, CO2 and H2 O are contained in it. To preliminarily investigate the influence of CO2 in the feed gas on CCHG, a mixture of H2 and CO2 with a CO2 concentration of 10% (denoted as H2  + CO2 ) was used for Co–Ca catalyzed coal hydrogasification at 850 °C and 3 MPa in a fluidized bed reactor. The results showed that the concurrence of coal hydrogasification with CO2 methanation produced CH4 efficiently. The CH4 yield (based on the carbon in coal) increased from 77.4% for pure H2 to 188% for H2  + CO2 within 120 min. More than 90% CO2 in situ conversion and 72.3% coal conversion were achieved. The catalytic effect of the Co–Ca loaded coal considerably improved the CH4 selectivity of CO2 methanation from 43.5% to 82.7%. The forms of Co and Ca in H2  + CO2 were consistent with those in pure hydrogen. The slow coal hydrogasification rate in H2  + CO2 was mainly attributed to the two-fold effects of CO2 methanation: the decrease in the partial hydrogen pressure and the competitive adsorption behavior of H2 and CO (a by-product of CO2 methanation) molecules on the cobalt active surface. This work provides a unique approach for simultaneously realizing the conversion of coal and the utilization of CO2 .